2019
DOI: 10.1038/s41419-019-1655-5
|View full text |Cite|
|
Sign up to set email alerts
|

c-kit Haploinsufficiency impairs adult cardiac stem cell growth, myogenicity and myocardial regeneration

Abstract: An overdose of Isoproterenol (ISO) causes acute cardiomyocyte (CM) dropout and activates the resident cardiac c-kit pos stem/progenitor cells (CSCs) generating a burst of new CM formation that replaces those lost to ISO. Recently, unsuccessful attempts to reproduce these findings using c-kit Cre knock-in (KI) mouse models were reported. We tested whether c-kit haploinsufficiency in c-kit Cre KI mice was the cause of the discrepant results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 45 publications
(106 reference statements)
1
74
0
2
Order By: Relevance
“…One lineage-tracing study reported a modest increase in c-Kit-expressing cardiomyocytes following TAC-induced PO, although the increase was below clinically-relevant levels 45 . However, genetic lineage-tracing Kit-Cre models that result in haploinsufficiency of the c-Kit gene have been questioned, as reviewed 46 49 . These may be addressed in the future by using a dual recombination system 48 .…”
Section: Discussionmentioning
confidence: 99%
“…One lineage-tracing study reported a modest increase in c-Kit-expressing cardiomyocytes following TAC-induced PO, although the increase was below clinically-relevant levels 45 . However, genetic lineage-tracing Kit-Cre models that result in haploinsufficiency of the c-Kit gene have been questioned, as reviewed 46 49 . These may be addressed in the future by using a dual recombination system 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expression of c-kit (a type III receptor tyrosine kinase) seems necessary. Indeed, c-kit haploinsufficiency in c-kit-deficient mice induced a falling myocardial repair after injury [ 33 ]. Furthermore, change of c-kit gene for Cre Recombinase expression in Cre/Lox genetic fate map animal models induced a detrimental c-kit haploinsufficiency that avoids efficient labeling of true CSCs and affects the regenerative capacity of these cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among resident stromal cells, a population of cardiac primitive cells (CPCs) is traceable in the adult human heart by means of different criteria [12][13][14][15][16], which can mediate CCT benefits through multiple biological mechanisms, including direct regeneration and, more importantly, angiogenic, anti-fibrotic, cytoprotective, and anti-inflammatory effects [17,18]. Multiple pathways and signals have been reported to affect the phenotype of CPCs [19][20][21][22][23][24][25]. Biological and functional changes occurring during cardiac adverse remodeling affect both ECM composition and architecture.…”
Section: Introductionmentioning
confidence: 99%